Tantric image of Shiva - Temples of India Project Team (Jio Institute, 2024)
This elegant Shaiva figure was part of a deva-kostha or sculptural niche placed on the walls of a now-lost Shaiva shrine and is now housed in the Government Museum, Sikar. The figure has four hands, with the upper two holding a skull-scepter and cobras. In his lower left hand, he holds a cup, or rather a skull, with the fingers of the right hand dipping towards the potion contained within it. On the left is an image of vyala, which was once placed in the salilantara recess of the temple wall. Iconographically, the figure suggests a tantric influence. The potion held in the cup/skull represents the spiritual nectar of the bliss attained after the completion of tantric sadhana in both Shaiva and Buddhist tantric traditions.